Lithotectonic Framework of the Core Zone, Southeastern Churchill Province, Canada - Corrigan, David; Wodicka, Natasha; McFarlane, Christopher; Lafrance, Isabelle; van Rooyen, Deanne; Bandyayera, Daniel; Bilodeau, Carl (Geoscience Canada, 2018)
The Core Zone, a broad region located between the Superior and North Atlantic cratons and predominantly underlain by Archean gneiss and granitoid rocks, remained until recently one of the less well known parts of the Canadian Shield. Previously thought to form part of the Archean Rae Craton, and later referred to as the Southeastern Churchill Province, it has been regarded as an ancient continental block trapped between the Paleoproterozoic Torngat and New Quebec orogens, with its relationships to the adjacent Superior and North Atlantic cratons remaining unresolved. The geochronological data presented herein suggest that the Archean evolution of the Core Zone was distinct from that in both the Superior and North Atlantic (Nain) cratons. Moreover, the Core Zone itself consists of at least three distinct lithotectonic entities with different evolutions, referred to herein as the George River, Mistinibi-Raude and Falcoz River blocks, that are separated by steeply-dipping, crustal-scale shear zones interpreted as paleosutures. Specifically, the George River Block consists of ca. 2.70 Ga supracrustal rocks and associated ca. 2.70–2.57 Ga intrusions. The Mistinibi-Raude Block consists of remnants of a ca. 2.37 Ga volcanic arc intruded by a ca. 2.32 Ga arc plutonic suite (Pallatin) and penecontemporaneous alkali plutons (Pelland and Nekuashu suites). It also hosts a coarse clastic cover sequence (the Hutte Sauvage Group) which contains detrital zircons provided from locally-derived, ca. 2.57–2.50 Ga, 2.37–2.32 Ga, and 2.10–2.08 Ga sources, with the youngest concordant grain dated at 1987 ± 7 Ma. The Falcoz River Block consists of ca. 2.89–2.80 Ga orthogneiss intruded by ca. 2.74–2.70 granite, tonalite, and granodiorite. At the western margin of the Core Zone, the George River Block and Kuujjuaq Domain may have been proximal by ca. 1.84 Ga as both appear to have been sutured by the 1.84–1.82 Ga De Pas Batholith, whereas at its eastern margin, the determination of metamorphic ages of ca. 1.85 to 1.80 Ga in the Falcoz River Block suggests protracted interaction with the adjacent Lac Lomier Complex during their amalgamation and suturing, but with a younger, ‘New Quebec’ overprint as well. The three crustal blocks forming the Core Zone add to a growing list of ‘exotic’ Archean to earliest Paleoproterozoic microcontinents and crustal slices that extend around the Superior Craton from the Grenville Front through Hudson Strait, across Hudson Bay and into Manitoba and Saskatchewan, in what was the Manikewan Ocean realm, which closed between ca. 1.83–1.80 Ga during the formation of supercontinent Nuna. RÉSUMÉ La Zone noyau, une vaste région située entre les cratons du Supérieur et de l’Atlantique Nord et reposant principalement sur des gneiss archéens et des roches granitiques, est demeurée jusqu’à récemment l’une des parties les moins bien connues du Bouclier canadien. Considérée auparavant comme faisant partie du craton archéen de Rae, puis comme la portion sud-est de la Province de Churchill, on l’a perçue comme un ancien bloc continental piégé entre les orogènes paléoprotérozoïques des Torngat et du Nouveau-Québec, ses relations avec les cratons supérieurs adjacents et de l’Atlantique Nord demeurant nébuleuses. Les données géochronologiques présentées ici permettent de penser que l’évolution archéenne de la Zone noyau a été différente de celle des cratons du Supérieur et de l’Atlantique Nord (Nain). De plus, la Zone noyau elle-même se compose d’au moins trois entités lithotectoniques distinctes avec des évolutions différentes, appelées ici les blocs de la rivière George, de Mistinibi-Raude et de la rivière Falcoz, lesquels sont séparées par des zones de cisaillement crustales à forte inclinaison, conçues comme des paléosutures. Plus précisément, le bloc de la rivière George est constitué de roches supracrustales d’env. 2,70 Ga, et d’intrusions connexes d’env. 2,70–2,57 Ga. Le bloc Mistinibi-Raude est constitué de vestiges d’un arc volcanique d’env. 2,37 Ga, recoupé par une suite plutonique d’arc d’env. 2,32 Ga (Pallatin) et de plutons alcalins péné-contemporains (suites Pelland et Nekuashu). Il contient également une séquence de couverture clastique grossière (le groupe Hutte Sauvage) renfermant des zircons détritiques de sources locales, âgés d’env. 2,57–2,50 Ga, 2,37–2,32 Ga et 2,10–2,08 Ga, le grain concordant le plus jeune étant âgé de 1987 ± 7 Ma. Le bloc de la rivière Falcoz est formé d’un orthogneiss âgé d’env. 2,89–2,80 Ga, recoupé par des intrusions de granite, tonalite et granodiorite âgées d’env. 2,74–2,70 Ga. À la marge ouest de la Zone noyau, le bloc de la rivière George et du domaine de Kuujjuaq peuvent avoir été proximaux il y a 1,84 Ga env., car les deux semblent avoir été suturés par le batholithe De Pas il y a environ 1,84–1,82 Ga, alors qu’à sa marge est, la détermination des datations métamorphiques de 1,85 à 1,80 Ga dans le bloc de la rivière Falcoz suggère une interaction prolongée avec le complexe adjacent du lac Lomier durant leur amalgamation et leur suture, mais affecté aussi d’une surimpression « Nouveau Québec » plus jeune. Les trois blocs crustaux formant la Zone noyau s’ajoutent à une liste croissante de micro-continents et d’écailles crustales « exotiques » archéennes à paléoprotérozoïques très précoces qui s’étalent autour du craton Supérieur depuis le front de Grenville jusqu’au Manitoba, à travers le détroit d’Hudson, la baie d’Hudson jusque dans le Manitoba et la Saskatchewan, là où s’étendait l’océan Manikewan, lequel s’est refermé il y a environ 1,83–1,80 Ga, pendant la formation du supercontinent Nuna.